MENGURANGI DAMPAK PANAS MATAHARI PADA DINDING KACA DENGAN â€œWATER FLOWâ€ - Ahsani, Muh Syukri; Mufida, Husna Noor; Aji, Mahardika Prasetya; Aji, Mahardika Prasetya; Sulhadi, Sulhadi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
The use of glass as a wall will cause the temperature in the room rose due to higher conduction and radiation from sunlight passing through the glass. So far, the impact of solar heat through the glass yan reduced by installing curtains or window film. In this study, water was supplied to the glass walls to reduce the impact of heat in the glass chamber. Research done by creating a miniature model house roofed and walled glass that is placed in the middle of the field during the sunny day. The water then flowed through the roof and walls of glass and made observations in the glass room temperature intervals of 30 seconds each. Temperatures inside the miniature house is then measured with a digital thermometer. Data analysis was done by plotting the relationship between the temperature inside the glass. Results obtained indicating that the air temperature in the glass room that flowed water is lower than without the flow of water, but the temperature difference obtained is not significant. Keywords: cooling, water, glass,greenhouse.